2013
DOI: 10.1038/nrneurol.2013.67
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of microRNAs in CNS injuries

Abstract: The consequences of injuries to the CNS are profound and persistent, resulting in substantial burden to both the individual patient and society. Existing treatments for CNS injuries such as stroke, traumatic brain injury and spinal cord injury have proved inadequate, partly owing to an incomplete understanding of post-injury cellular and molecular changes. MicroRNAs (miRNAs) are RNA molecules composed of 20–24 nucleotides that function to inhibit mRNA translation and have key roles in normal CNS development an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
209
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(210 citation statements)
references
References 139 publications
(153 reference statements)
1
209
0
Order By: Relevance
“…n.s., Not significant. binding proteins and/or microRNAs (Barrett et al, 2012). A prior report has shown that serial truncation of the 3ЈUTR of p75 NTR leads to significantly higher levels of p75 NTR protein, thus implicating regulation of p75 NTR by its 3ЈUTR (Krygier and Djakiew, 2001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…n.s., Not significant. binding proteins and/or microRNAs (Barrett et al, 2012). A prior report has shown that serial truncation of the 3ЈUTR of p75 NTR leads to significantly higher levels of p75 NTR protein, thus implicating regulation of p75 NTR by its 3ЈUTR (Krygier and Djakiew, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…All procedures were performed in accordance with institutional and federal guidelines for the treatment of animals. Focal cerebral ischemia was induced using the intraluminal filament model of middle cerebral artery occlusion (MCAO), as described previously (Abe et al, 2010;Jackman et al, 2011;Hochrainer et al, 2012). All experiments were performed in male C57BL/6 mice (6 -8 weeks) or p75 NTR Ϫ/Ϫ mice, which were purchased from the Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Even a single miRNA is known to regulate the entire mRNA network [78], and is expected to be used in therapeutics by blocking the pathophysiological cascade after brain injury. In particular, miRNAs are abundantly expressed in the brain tissue, and some are known to have brain-specific functions [79][80][81]. After brain injury, miRNA expression levels are known to vary significantly [82,83], with the downregulation of miR-23a and miR-27a being confirmed within 4 hours of the brain injury.…”
Section: Gfapmentioning
confidence: 99%
“…Functional changes to the mu opioid receptor (MOR) have been observed following SCI, providing a potential explanation for why pain mitigation with opioids may be unsuccessful [12]. However, the mechanism behind these changes is not well understood MicroRNAs, small noncoding RNAs, are an emerging player in the field of pain research and have the potential to elucidate the chronic pain sequela associated with SCI at cellular level [13][14][15][16][17][18][19]. The Let-7 family of miRNAs has specifically been shown to target MOR, suggesting its link to opioid tolerance [20].…”
Section: Introductionmentioning
confidence: 99%